SIGNIFICANCE OF PRODUCTION FACTORS IN PRODUCTIVITY MEASUREMENTS IN AGRICULTURE (Theory aspects) - D. Drobac, Milorad (Economics of Agriculture, 2008)
In his work author preview theory aspect of significance of production factors in measurement altogether productivity in agriculture, simultaneously pointing on problems that are very present here and more complex then in other activities of material output. Natural factors of production in agriculture emphasizly affect on altogether productivity. Many authors wrote about that with aspiration that they come to adequate concept of calculation productivity markers. Development of procedure for calculating markers of aggregates productivity in agriculture is based on calculated indexes altogether output and altogether input in their puting on interrelation, that makes measure of aggregate productivity. Laspeyres index of quantity and Tornquist index as approach to "Divisia index" that is used as index of logaritham of modification are especially analyzed in this work.